Model-free and Model-based Learning as Joint Drivers of Investor Behavior - Barberis, Nicholas,Jin, Lawrence J. (National Bureau of Economic Research, 2023)
In the past decade, researchers in psychology and neuroscience studying human decision-making have increasingly adopted a framework that combines two systems, namely
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Anlageverhalten; Meinung; Lernprozess; Verhaltensökonomik; Behavioral Microeconomics: Underlying Principles; Behavioral Finance: Underlying Principles; Portfolio Choice; Investment Decisions